Pengaruh Size, Age, Profitability, Leverage dan Sales Growth Terhadap Tax Avoidance - Amanda Dhinari Permata; Siti Nurlaela; Endang Masitoh Wahyuningsih (Jurnal Akuntansi dan Pajak, 2018)
The purpose of this study was to examine the effect of Size, Age, Profitability, Leverage, Sales Growth on Tax Avoidance. The population which is the object of this research is the basic and chemical industry sectors listed on Indonesia Stock Exchange (BEI) in 2012 - 2016. The total population of 68 companies, this study obtained by purposive sampling technique which then resulted in 32 research samples for further investigation. The analysis technique used is logistic regression analysis. Based on data analysis and discussion can be concluded that Size, Age, Profitability, Leverage, and Sales Growth has no effect on Tax Avoidance. This means that the government succeeded in conducting Tax Amnesty program which has the impact of the company will not do Tax Avoidance